(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
In the modern context of the emerging digital economy, the global scarcity of economic resources and the continuously growing human needs are not only characteristic features of the world economy as a whole, but also turn the formation of an innovative economy into an objective necessity for many countries around the world. Today, the socio-economic development paradigm focused on implementing innovations across various sectors of the economy and market segments is regarded as a strategic priority for every nation. From this perspective, considering national specificities, the examination of food security and its logistical support - aimed at ensuring the stable and guaranteed provision of the population with essential resources amid the development of an innovative economy and the intensification of globalization and integration processes is of great importance and current relevance. Keywords: innovative economy, economic security, food security, food market, national food system, logistical infrastructure of the food market, logistics costs.